Hydrodynamic excitation spectrum and time correlation functions for the multicomponent mixtures of magnetic and nonmagnetic particles - Batsevych, O.F.; Mryglod, I.M.; Rudavskii, Yu.K.; Tokarchuk, M.V. (Condensed Matter Physics, 2001)
The hydrodynamics of a multicomponent mixture of magnetic and nonmagnetic particles is investigated. The hydrodynamic modes spectrum is obtained. It is shown that two collective modes are responsible for the propagation of sound while the other ones ( j − 2 modes, where j is determined by the number of additive integrals of motion) are purely diffusive. The analytical expressions for all the hydrodynamic time correlation functions are derived and written via the well-defined thermodynamical quantities and transport coefficients of the system. Based on this, the expressions for the dynamical structure factors for a binary magnetic mixture in the paramagnetic state and for a three-component nonmagnetic mixture are derived.